The Role of Emotion Regulation as a Mediator between Empathy and Bullying Behavior in Junior High School Students - Putri, Riska Dwi; Ariyati, Ika; Setiawan, Agus (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2026)
Bullying behavior among junior high school students is a serious issue that can negatively affect the psychological development of both victims and perpetrators. However, studies specifically examining the role of emotion regulation as a moderator in the relationship between empathy and bullying behavior among junior high school students remain limited. Therefore, this study aimed to examine emotion regulation as a moderator of the relationship between empathy and bullying behavior among junior high school students. This study employed a quantitative approach with a moderation regression design. The participants were 223 students from SMP Ma’arif 1 Metro, selected using a total sampling technique. The research instruments included the Empathy Scale (Indonesian version of EmQue-CA, α = 0.96), the Emotion Regulation Scale (α = 0.865), and the Bullying Behavior Scale (α = 0.88). Data analysis was conducted using moderated regression analysis in SPSS version 21. The findings revealed that empathy did not have a significant effect on bullying behavior (p = 0.285 > 0.05). However, emotion regulation significantly moderated the relationship between empathy and bullying behavior (p = 0.000 < 0.05). The R Square value of 0.888 indicated that empathy and emotion regulation contributed 88.8% to bullying behavior. These findings demonstrate that emotion regulation serves as a moderating variable, strengthening the relationship between empathy and bullying behavior among junior high school students. The practical implication of this study is the importance of integrating empathy and emotion regulation development programs into school bullying prevention efforts.